Assessing the Impact of NAADS Programme on Agricultural Economic Performance in Mbarara District - Uganda - K., Tamson Nuwagaba; R., Firimooni Banugire; R., Nuwabiimpa Milton (Bus Eco J, 2018)
This study was conducted on assessing the impact of NAADS programme on agricultural economic performance in Mbarara district. Agricultural Economic performance was assessed in terms of household income and commercialization. The study was done in two Sub-Counties i.e., Nyamitanga and Mwiizi S/County to represent Mbarara district. A sample of 132 respondents was used of both NAADS and Non-NAADS farmers in both Goat rearing and Piggery and NAADS Coordinators who were involved in the programme from the district to Parish level in Mbarara district. Both stratified and purposive sampling were used to select the sample in both Mwiizi sub-county and Nyamitanga division as, 63 NAADS farmers of both enterprises (goat and pig rearing) and 6 NAADS Coordinators from two S/Counties as well as 63 Non-NAADS farmers from the same enterprises in both sub-counties. The study used both questionnaire survey and interview methods in collecting data from the field. The study adopted a Quasi-experimental research design where difference in difference model was used. The Difference between means was used to determine if there is a significant difference between NAADS and NonNAADS on economic outcomes of commercialization and household income in Mbarara district. The primary data was collected using questionnaire survey and interview methods and analyzed using SPSS. The findings show that there was no significant difference on level of commercialization in terms of technology adoption; household income in both NAADS and Non-NAADS farmers involved in goat rearing and piggery in Mbarara district. Basing on the findings, the level of monitoring and supervision, distribution of farm inputs and service delivery, fund flows to facilitate the coordinators and service providers, and purchase inputs, farm inputs to distribute to farmers, attitude of farmers towards government programmes and corruption and embezzlement of funds were the most important factors that greatly affected the economic performance of NAADS programme in Mbarara district. In recommendation, the government should increase the level of monitoring and supervision at different levels, increasing in the accessibility of inputs and service delivery, anti-corruption and embezzlement laws, allocation of enough funds, empowerment of the institutions like the local government, farmer groups and other civil society organisations (CSOs), increase on the level of accessibility through fair distribution of farm inputs and encourage pilot studies in area where the programme is to be implemented
Keywords: Economic; Agro-industrial; Farmer